Validity of rapid estimates of household wealth and income for health surveys in rural Africa - Morris, Saul Sutkover; Carletto, Calogero; Hoddinott, John F.; Christiaensen, Luc (International Food Policy Research Institute, 1999)
Drawing data from four different integrated household surveys in rural areas of Mali, Malawi, and two national surveys in Côte d’Ivoire, this paper tests the validity of proxy measures of household wealth and income that can be readily implemented in health surveys in rural Africa. The assumptions underlying the choice of wealth proxy are described, and correlations with the true value are assessed in two different settings. The expenditure proxy is developed and then tested for replicability in two independent data sets representing the same population. The study found that in both Mali and Malawi, the wealth proxy correlated highly (r $ 0.74) with the more complex monetary value method. For rural areas of Côte d’Ivoire, it was possible to generate a list of just 10 expenditure items, the values of which, when summed, correlated highly with expenditures on all items combined (r = 0.74, development data set; r = 0.72, validation data set). Total household expenditure is an accepted alternative measure of household wealth and income in developing country settings. This paper thus shows that it can be feasible to approximate both household wealth and expenditures in rural African settings without dramatically lengthening questionnaires whose primary focus is on health.